Clinical characterization of post-surgical outcomes and associated risk factors of lipomyelomeningocele in Eastern India - Devansh Mishra; Subhasis Ghosh; Shubhamitra Chaudhuri (Asian Journal of Medical Sciences, 2025)
Background: Lipomyelomeningocele (LMMC), the most complex spinal lipoma and a common spinal malformation, can cause complications ranging from bladder dysfunction to significant neurological deficits. Therefore, prompt diagnosis and treatment are essential. Aims and Objectives: The study aims to determine post-operative complications, functional outcomes, and risk factors in LMMC patients. Materials and Methods: This prospective observational study included 40 LMMC patients who underwent surgery, regardless of age and sex. Demographic, clinical, pre-operative, radiological, intraoperative, and post-operative data were recorded. Patients were followed for 4 months to assess complications (early and late) and risk factors associated with them. Results: Of 40 patients, most were 0–3 years with male predominance (57.5%). The lumbosacral region (47.5%) was the most common anatomical site, and transitional lipoma was the most frequent type (40%). Detethering was performed in all 40 patients, with total lipoma excision achieved in 67.5%. Post-operative complications occurred in 42.5% (17 patients): 13 experienced early complications (cerebrospinal fluid leak [7], infection [4], wound dehiscence [2]), and four experienced late complications (neurological deficit [1], pseudomeningocele [3]). Clinically, 7.5% of patients had developed new neurological deficits. Factors associated with complications included: Age 3–6 years (P=0.02), A-positive blood type (P=0.01), lumbosacral/sacral location (P=0.014), dorsal/chaotic/terminal lipoma type (P<0.001), and partial lipoma excision with iatrogenic injury (P=0.001) using a patching technique (P=0.001). Post-operative proning reduced the risk of complications (P<0.001). Conclusion: Our study demonstrates that detethering with complete lipoma excision, dural closure using glue, and post-operative proning improve outcomes and reduce post-operative complications in LMMC patients.